2016
DOI: 10.1016/j.eurpsy.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Vulnerability for Psychosis: Meta-Analysis of Environmental Risk Factors for Psychosis in Subjects at Ultra High-Risk

Abstract: The increased vulnerability of UHR subjects can be related to environmental risk factors like childhood trauma, adverse life events and affective dysfunction. The role of genetic and epigenetic risk factors awaits clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
203
3
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(236 citation statements)
references
References 105 publications
10
203
3
7
Order By: Relevance
“…As expected, UHR individuals in our sample were more frequently unemployed, lived with their families and were single, which fits with the literature (Brandizzi et al, ; Fusar‐Poli et al, ; Fusar‐Poli et al, ). Lower rates of employment were also found in UHR with lower social adaptation.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, UHR individuals in our sample were more frequently unemployed, lived with their families and were single, which fits with the literature (Brandizzi et al, ; Fusar‐Poli et al, ; Fusar‐Poli et al, ). Lower rates of employment were also found in UHR with lower social adaptation.…”
Section: Discussionsupporting
confidence: 92%
“…Current literature and reviews (Fusar‐Poli et al, ; Gibson, Alloy, & Ellman, ) have shown trauma to be an important risk factor among those at high risk of psychosis. Interestingly, although our sample all met criteria for being at CHR, we found a further distinction between those with and without a family history.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of trauma has consistently been reported in UHR samples (Addington et al, ; Bechdolf et al, ; Fusar‐Poli et al, ; Kraan, Velthorst, Smit, de Haan, & van der Gaag, ). Russo et al () found that those at high risk for psychosis experienced trauma at an earlier age, and a greater number of total traumas, compared to healthy controls.…”
Section: Introductionmentioning
confidence: 87%